Effectiveness of black crab (scylla serrata) chitosan gel in inhibiting the growth of Candida albicans in vitro: experimental study - Pradiva, Muhammad Naufal; Rusdy, Hendry; Agusnar, Harry (Fakultas Kedokteran Gigi Universitas Padjadjaran, 2025)
ABSTRACTIntroduction: Chitosan is a polymer biomaterial obtained by deacetylation of chitin which is widely used for various processed products. Chitosan can inhibit the growth of Candida albicans, which is one of the fungi that play a role in the process of dental caries. The purpose of this study was to analyze the effectiveness of black crab (Scylla serrata) chitosan gel in inhibiting the growth of Candida albicans. Methods: This study used a laboratory experimental method with a posttest only control group design. The sample used in this study was Candida albicans ATCC 10231 preparation. The study was conducted using a disc diffusion method to test the inhibition of black crab chitosan gel 0.5%, 1%, 1.5%, 2%, 2.5% against Candida albicans. The data analysis technique used was One-way ANOVA. Results: The inhibition of Scylla serrata chitosan gel with a concentration of 0.5% has no inhibition against Candida albicans. However, it is different with Scylla serrata chitosan gel with a concentration of 1%, 1.5%, 2%, 2.5% has inhibition against Candida albicans. The inhibition of the positive control group (ketoconazole) was more effective in inhibiting Candida albicans than the chitosan gel at concentrations of 1%, 1.5%, 2%, and 2.5%. Conclusion: Chitosan gel derived from Scylla serrata has the ability to inhibit the growth of Candida albicans. This finding indicates the potential of chitosan gel as an effective antifungal agent, which can be used in the development of therapies to treat fungal infections.KEY WORDS: Antifungal, Candida albicans, black crab chitosan (scylla serrata), chitin, cariesEfektivitas daya hambat gel kitosan kepiting hitam (scylla serrata) terhadap pertumbuhan candida albicans secara in vitro : Studi eksperimentalABSTRAKPendahuluan: Kitosan merupakan biomaterial polimer yang diperoleh dengan deasetilasi kitin yang banyak dimanfaatkan untuk berbagai macam produk olahan. Kitosan dapat menghambat pertumbuhan jamur Candida albicans yaitu salah satu jamur yang berperan dalam proses terjadinya karies gigi. Tujuan Penelitian ini adalah untuk menganalisis efektivitas gel kitosan kepiting hitam (Scylla serrata) dalam menghambat pertumbuhan Candida albicans. Metode: Penelitian ini menggunakan metode eksperimental laboratorium dengan desain kelompok kontrol post-test only. Sampel yang digunakan dalam penelitian ini adalah sediaan Candida albicans ATCC 10231. Penelitian dilakukan menggunakan metode disc diffusion method untuk menguji daya hambat gel kitosan kepiting hitam 0,5%, 1%, 1,5%, 2%, 2,5% terhadap Candida albicans. Teknik analisis data yang digunakan yaitu One-way ANOVA. Hasil: Daya hambat gel kitosan Scylla serrata dengan konsentrasi 0,5% tidak memiliki daya hambat terhadap Candida albicans. Namun berbeda dengan gel kitosan Scylla serrata dengan konsentrasi 1%, 1,5 %, 2 %, 2,5 % memiliki daya hambat terhadap Candida albicans. Daya hambat kelompok kontrol positif (ketoconazole) lebih efektif dalam menghambat Candida albicans dibandingkan dengan gel kitosan pada konsentrasi 1%, 1,5%, 2%, dan 2,5%. Simpulan: Gel kitosan yang berasal dari Scylla serrata memiliki kemampuan untuk menghambat pertumbuhan Candida albicans. Temuan ini mengindikasikan potensi gel kitosan sebagai agen antijamur yang efektif, yang dapat digunakan dalam pengembangan terapi untuk mengatasi infeksi jamur.KATA KUNCI: Antijamur, Candida albicans, kitosan kepiting hitam (scylla serrata), kitin, karies